Visual Methods in Migration Studies: new possibilities, theoretical implications, and ethical questions - Desille, Amandine (2019)
The purpose of this brief is to reflect critically on the use of visual methods in migration studiesand to provideconcrete examples of their application. We propose to think of the adoption of a visual methodology as a way to access and produce knowledge within the field of migration studies, rather than relying on disciplinaryframing. Based on a collection of empirical cases, we show that researchers can mobilise still and movingimages in the context of knowledge production.Specifically addressed in this brief are mental maps.In the field of migration studies, visual methods generate new possibilitiesfor data collection and their analysis. Nevertheless, questions pertaining to methodological challenges,theoretical implications, as well as ethics remain. This briefis based on a volume entitled “Visual Methods in Migration Studies: new possibilities theoretical implications, and ethical questions”, currently in the process of edition. The proposal has won the IMISCOE competitive book for call last fall, and publication is foreseen in 2020